FAKTOR - FAKTOR YANG MEMPENGARUHI KUALITAS SISTEM INFORMASI AKUNTANSI - Afrida, Anggrelia; Aprianto, Aprianto; Rahmadona, Cahaya (Universitas Muhammadiyah Palembang, 2024)
The purpose of the research was to identify and analyze the factors that effect on the Quality of Accounting Information System at PT. Madhani Talatah Nusantara Muara Enim, South Sumatra, using primary data. The research uses interviews and questionnaires as data collection techniques. The population of the research was 46 respondents with the sampling technique is using the saturated sampling. The data analysis method used in this study is quantitative analysis with descriptive statistical techniques and inferential statistics. The inferential statistics techniques consists of consisting of classical assumption tests, multiple regression analysis, coefficient of determination, and hypothesis testing designs, assisted by the Statistical Product and Service Solutions (SPSS) software. The results of this research indicate that the factors influencing the quality of the accounting information system include internal control system, user competence, and information technology.